Elderly patients have more infectious complications following laparoscopic colorectal cancer surgery. (January 2016) - Kvasnovsky, C. L.; Adams, K.; Sideris, M.; Laycock, J.; Haji, A. K.; Haq, A.; Nunoo‐Mensah, J.; Papagrigoriadis, S.
Abstract: Aim: Elderly patients may be at higher risk of postoperative complications, particularly infective, than younger patients. Method: We prospectively followed 163 consecutive patients undergoing elective laparoscopic resection for cancer. We compared patients < 65, 65–80 and > 80 years of age at the time of surgery. Results: Seventy (42.9%) patients had no complication; 93 (57.1%) had at least one complication following surgery and in 20 (12.3%) this was major. There was no difference in major complications between the groups ( P = 0.47). Patients over 65 years of age were more likely to have a complication of any severity [< 65 years, 39.3%; 65–80 years, 69.3%; and > 80 years, 63.0% ( P = 0.002)]. The frequency of gastrointestinal complications (30.1%) was similar in the groups ( P = 0.29), as was wound infection (25.2%) ( P = 0.65). There was an increase in the frequency of infectious complications, especially chest infection, with age, from 14.8% in patients < 65 years, to 22.7% in patients 65–80 years, to 44.4% in patients > 80 years ( P = 0.01). Multivariate analysis showed no increase in overall complications in elderly patients, but Stage II or Stage III cancer (OR = 2.59, P = 0.04) and increasing body mass index (BMI) (OR = 1.07 for each unit increase in BMI, P = 0.04) were related to complications. Age remained the only predictor of an infective complication on multivariate analysis. Patients > 80 years of age had 4.21 times the OR of an infective complication ( P = 0.03). Conclusion: Older patients are more susceptible to infective complications postoperatively, particularly chest complications. Surgeons should alter their practice to reduce morbidity, such as adopting protocols requiring early physiotherapy.